An Exploration of Some Predictors of Quality of Life-Related to the Innate Immune System, Inflammation, and Disease Activity in Patients with Behcet's Syndrome: An Analytical Cross-sectional Study - Faghfouri, Amir H.; Shoura, Seyyed M. S.; Papi, Shahab; Khabbazi, Alireza; Baradaran, Behzad; Badpeyma, Mohaddeseh; Faghfuri, Elnaz (Current Rheumatology Reviews, 2024)
Background: Behçet's disease (BD) has a growing prevalence in Silk Road countries. The aim of our cross-sectional study was to explore the clinical and molecular predictors of quality of life in BD patients. Materials and Methods: One hundred and fifty consecutive Iranian BD patients with an age range between 20-50 years were included. The Leeds Behçet's disease quality of life (BDQoL) in Persian form was fulfilled to evaluate the quality of life. Anthropometric measurements were carried out using the calibrated scales. Iranian Behcet's Disease Dynamic Activity Measure (IBDDAM), Behcet's disease current activity form (BDCAF), and Total Inflammatory Activity Index (TIAI) were used to assess BD activity. mRNA expression of toll-like receptors 2 and 4 (TLR2 and TLR4) and tumor-necrosis-factor-alpha (TNF-α) levels in serum were measured by real-time polymerase chain reaction (PCR) and ELISA, respectively. Multiple linear backward regression at P = 0.1 was used to study the potential predictors of quality of life. Results: TLR2 and BDCAF were shown to be the most important predictors of quality of life in BD patients by 22%. There were positive associations between them (β = 0.326, p = 0.013 for BDCAF; β = 0.366, p = 0.006 for TLR2) and BDQoL value. Conclusion: Higher TLR2 expression as a key protein in recognizing pathogens by innate immunity and BDCAF value as a comprehensive BD assessing scale contribute to poor quality of life among BD patients. Emphasizing therapeutically, approaches associated with lower TLR2 expression and BDCAF value can be considered in future studies.
Keywords: tumor necrosis factor-alpha